2020
DOI: 10.1136/bmjdrc-2019-000977
|View full text |Cite
|
Sign up to set email alerts
|

Levels of ankle–brachial index and the risk of diabetes mellitus complications

Abstract: ObjectiveWe sought to compare the association of categorized ankle–brachial index (ABI) with mortality and complications of diabetes in persons with no symptoms of peripheral arterial disease (PAD) and in primary cardiovascular disease prevention.Research design and methodsThis is a retrospective cohort study of persons with type 2 diabetes aged 35–85 years, from 2006 to 2011. Data were obtained from the Sistema d'Informació per al Desenvolupament de la Investigació en Atenció Primària (SIDIAPQ). Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
0
25
0
1
Order By: Relevance
“…ROC results revealed that the combination of ABI and baPWV may improve risk classification in predicting all-cause and expanded CVD mortality in patients with T2DM. ABI and baPWV are simple, non-invasive, economical, and realistic measures that have become increasingly important in predicting mortality [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . Most studies exploring the associations of ABI and/or baPWV with mortality in T2DM population [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] only considered ABI alone [28][29][30][31][32][33][34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROC results revealed that the combination of ABI and baPWV may improve risk classification in predicting all-cause and expanded CVD mortality in patients with T2DM. ABI and baPWV are simple, non-invasive, economical, and realistic measures that have become increasingly important in predicting mortality [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . Most studies exploring the associations of ABI and/or baPWV with mortality in T2DM population [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] only considered ABI alone [28][29][30][31][32][33][34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%
“…Only two works considered baPWV alone 43,44 , and another two simultaneously considered ABI and baPWV 45,46 . As a consequence, the findings on the association between ABI and mortality were inconsistent [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . Significant associations were observed in some studies [28][29][30][31][32][33][34][35][36][37][38][39][40] but not in others 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“… 7 Ankle brachial index (ABI) is a non-invasive tool for detecting vascular status and for measuring lower leg arteries versus upper leg arterial health status. 8 ABI is the ratio between the lower limb (ankle) systolic blood pressure and the upper limb (upper arm) systolic blood pressure. ABI reflects vascular resistance, which explains the main factors: the blood vessel diameter, which can be narrowed either from internal factors (plaque and intimal tearing) or from external factors, such as compression by soft tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Association of different categories of ABI in a large group of type II diabetics over a period of 6 years showed a high incidence of mortality and acute myocardial infarction, suggesting the importance of preventive measures in such persons. [ 8 ] The prevalence of PAD has been recorded in various studies differently. It was relatively lower (13.7%) when only early type II diabetes patients were included who did not have any previously diagnosed complications.…”
Section: Discussionmentioning
confidence: 99%